The influence of changing from fluorenone to fluorenyl-malonitrile on the excited state dynamic of tetraphenylbenzene-fluorene based donor-acceptor systems - Sutton, Joshua (2020)
Understanding the photophysical properties of a donor-acceptor system, and how it is linked to and controlled by structural modification is key to the systematic design of new materials to fulfil a particular role. In this study two series of tetraphenylbenzene-fluorene based donor-acceptor systems are compared. Between the series the fluorene unit is changed from fluorenone to fluorenyl-malonitrile. The series with the fluorenone acceptor (series 1) was found to show high environment sensitivity and green emission (530 nm). By adding the more electron withdrawing malonitrile the electronic absorbance and emission was red shifted, with the absorbance moving from the UV region to blue region and emission shifting to 650 nm. However, the near complete quenching of the emission was also observed.